Perspectives on East Asia - SAGIYAMA, Ikuko; Pedone, Valentina (Studi e saggi, 2014)
This volume is a collection of eight articles by different scholars from Japan, China, and Italy. Although the topics covered belong to different fields, such as literature, history, linguistics and sociology, all of the included works are geographically focused on cultural aspects of East Asia. The interdisciplinary character of the collection is meant to provide a broader perspective on the cultures and societies of the Far East, nonetheless the individual articles are each based on specific and focused research. The authors featured in the volume are Eduardo Barberis, Edoardo Gerlini, Tiziana Lioi, Massimiliano Tomasi, Pierantonio Zanotti, Tanina Zappone and Zhou Yuhui. The volume is also proud to include a short piece by professor Takei Kyōzō on Omowaku utaawase.